The Lutheran "Faustus" in Foxe's Acts and Monuments - Brljak, Vladimir (Array, 2010)
The article examines the account, found in the 1570 second edition of John Foxe’s Acts and Monuments, of a young Wittenberg sorcerer who makes a pact with the devil, exchanging his soul for worldly gains, but is saved from damnation by the intercession of Martin Luther. It is argued that his neglected passage, which predates any of the existing Faust sources, sheds new light on the much debated question of the origins of the Faust legend.